Garden waste management: Process and cost - Zakareta, Mohd Mustaki; Mohd Shafie, Shafini (2017)
Garden waste is a blend of organic such as flowers, grass clippings, branches and wood and non-organic such as soil that is produced during the maintenance of public parks and small gardens.Garden waste generation and constantly changing depending on location and season.In Malaysia, garden waste management managed by Municipal Council as well as private companies.This study will be obtained qualitatively by seeking information through interviews with company Enviroment EIdaman Sdn Bhdwhich manages garden waste all areas of Kedah.Therefore, this study was able to identify the processes that are carried out to manage the garden waste as well as evaluate the cost of each of these processes. Expected result may show the cost of process garden waste are high.